AKUNTABILITAS PELAYANAN PRIMA DI KECAMATAN BUMIAJI KOTA BATU - Exnasius Maisilalahi; Sugeng Rusmiwari (Universitas Tribhuwana Tunggadewi, 2019)
Abstract: Accountability become increasingly popular in the center of problems public service today. Accountability also is part of key principles in realize good governance (good governance). The state apparatus as public servants head of is that the whole the institutions as well as a number of state officials and the government of the state of which includes the will involve all stakeholders namely state of the nation address and in the government as the man of the state of me and the man of the community. Was used in the study qualitative research was conducted. A small sample of the research uses snowball technique were the sampling method of with several informants, the technique of data collection was carried out by researchers of bond issuance will be; observation, the objective of the interview and documentation of a method of data available for analysis to be used that is descriptive of who describes the results of data obtained the fire victims group of researchers from. The results of research suggests that it is accountability a prime service in subdistrict Bumiaji the city of stone it can be said already good, as follows; accountability a prime service are men who are a the lump bones and we that had already been decided that their main activity must be able to be the state administration accounted to the community on the great commission nor the people as whom ultimate sovereignty is in accordance with law which is valid for five. Accountability a prime service as a commodity the public report on basic (the public report on basic good) that which is given by the government had already it should be it has accompanied by good service quality to the rest of us, so that of the Indonesian people would have more confidence to the government. Key words: accountability, a prime service, good governance. Abstrak: Akuntabilitas menjadi kian populer ditengah permasalahan pelayanan publik dewasa ini. Akuntabilitas juga merupakan bagian dari prinsip dalam mewujudkan pemerintahan yang baik (good governance). Aparatur negara sebagai pelayan masyarakat adalah keseluruhan lembaga dan pejabat negara serta pemerintahan negara yang meliputi aparatur kenegaraan dan pemerintahan sebagai abdi negara dan abdi masyarakat.. Penelitian ini menggunakan metode penelitian kualitatif. Sampel penelitian menggunakan Snowball sampling dengan beberapa informan, teknik pengumpulan data dilakukan oleh peneliti yakni; observasi, wawancara dan dokumentasi metode analisa data yang digunakan yakni deskriptif yang mendeskripsikan hasil data yang diperoleh peneliti. Hasil penelitian membuktikan bahwa Akuntabilitas Pelayanan Prima Di Kecamatan Bumiaji Kota Batu dapat dikatakan sudah baik, sebagai berikut; Akuntabilitas pelayanan prima merupakan suatu asas yang menentukan bahwa kegiatan penyelenggaraan negara harus dapat dipertanggungjawab kepada masyarakat ataupun rakyat sebagai pemegang kedaulatan tertinggi negara sesuai dengan UU yang berlaku. Akuntabilitas Pelayanan Prima sebagai komoditas public (Public Good) yang diberikan oleh pemerintah sudah semestinya dibarengi dengan kualitas pelayanan yang baik untuk masyarakat, sehingga masyarakat akan menaruh kepercayaan kepada pemerintah. Kata Kunci: Akuntabilitas, Pelayanan Prima, Good Governance